A Novel Penalty Scheme in Genetic Algorithms For Structural Design Optimization - Pruettha Nanakorn; Konlakartn Meesomklin (ASEAN Journal on Science and Technology for Development, 2000)
A Novel Penalty Scheme in Genetic Algorithms For Structural Design Optimization